The stages of religious education at the establishments of public secondary education of FRG in 1945-2012 (Pedagogy of Higher and Secondary Education, 2012)
Arterchuk T.O. The stages of religious education at the establishments of public secondary education of FRG in 1945-2012.In the article an attempt has been made to determine the stages of religious education at the establishments of public secondary education of FRG in 1945-2012; it defined historical frames of every stage, determined key events which influenced the course of religious education, named methodological bases, teachers who made an important contribution into religious education, analyzed qualitative and quantitative changes which took place in every stage of religious education.
Keywords: stages of religious education of schoolchildren; German religious pedagogy; criteria of division into periods